(untitled) (Journal of Surgical Sciences, 2019)
Although gastrointestinal stromal tumors (GISTs) frequently occur in the gastrointestinal tract, they are relatively rare in the rectum. Biopsy of the lesion and immunohistochemistry (IHC) confirm the diagnosis. Complete surgical resection is the principal curative procedure. In combination with surgery, immunotherapy with Imatinib shows cure in intermediate risk and improvement in high risk rectal GIST. We report a case of a 45-yearold female who presented with constipation and generalized weakness, ultimately diagnosed to have rectal GIST. Journal of Surgical Sciences (2015) Vol. 19 (2) : 85-88